Olfactory adaptation depends on the Trp Ca[2+] channel in Drosophila. - Stortkuhl, K.F.; Hovemann, B.T.; Carlson, J.R. (Journal of Neuroscience, 1999)
Olfactory adaptation is shown to occur in Drosophila, at both behavioral and physiological levels. In a behavioral paradigm, the extent of adaptation is shown to depend on the dose and duration of the adapting stimulus. Half-maximal adaptation occurred after 15 sec of exposure to an odor, and recovery occurred with a half-time of 1. 5 min, under a set of test conditions. Cross-adaptation was observed among all odor combinations tested, although to a lesser extent than when the same odor was used as both the adapting and the test stimulus. Mutants of the transient receptor potential (Trp) Ca2+ channel were normal in olfactory response, but defective in olfactory adaptation, when measured either behaviorally or in tests of antennal physiology. These results indicate that olfactory response and adaptation can be distinguished. Trp expression was detected in the developing antenna but, surprisingly, not in the mature antenna. These results, together with temperature-shift analysis of a temperature-sensitive trp mutant, provide evidence of a role of Trp in olfactory system development.